Implementasi Profil Pelajar Pancasila di Sekolah Dasar - Sari, Diana Ayu Puspita; Sulistiyo, Urip; Sofwan, Muhammad (Universitas Batanghari Jambi, 2024)
In a study related to the implementation of the Pancasila student profile in driving schools, it was found that students in driving schools had a good understanding of the Pancasila student profile. However, other facts also show that the implementation of the Pancasila student profile is not only happening in driving schools but has started to be implemented in non-moving schools. This creates a gap between previous research and the reality on the ground. The aim of this research is to describe the habits made by teachers in implementing the Pancasila student profile values of faith, devotion to God Almighty, and noble character in class IV A at State Elementary School 80/I Muara Bulian. This research was carried out at SD Negeri 80/I Muara Bulian in the odd semester of the 2023/2024 academic year. Research data was obtained through observation, interviews and document study. The results of this research show that the Pancasila student profile of the faith dimension, being devoted to God Almighty has been implemented at SDN 80/I Muara Bulian. The research results show that the implementation stage through project activities has been implemented in line with what is stated in the Ministry of Education and Culture 2020. The implementation of the Pancasila student profile is implemented well through routine and spontaneous habits. The habituation carried out is able to develop students' character who is religious and has noble character. This is in line with the main characteristics of the Pancasila student profile.